The magician$1 (Bs boy s - Cooper, Susan, 1935-; Riglietti, Serena (New York : Margaret K. McElderry Books, 2005)
A boy who works for a magician meets familiar fairy tale characters when he is transported to the Land of Story in search of a missing puppet.
Keywords: Fairy tales; Characters in literature -- Fiction; Puppets -- Fiction; Puppet theater -- Fiction; Magicians -- Fiction